Bantuan Demokrasi dalam Perspektif “Jepang Baru”: Suatu Analisis terhadap Diplomasi Demokrasi Jepang - Ishaq Rahman (WANUA : Jurnal Hubungan Internasional, 2015)
AbstractAs a country with a stable capacity in economic, Japan's role in international development is shown by becoming a major donor countries through the mechanism of Official Development Assistance (ODA). However, various dynamics of international relations post-World War II had pushed Japan to engage further, beyond the limits which set out in constitution 1947 about military and defense. This article analyzes how Japan put diplomacy of democracy as a vision to actualize the "New Japan", which is a state construction with total involvement in the international world.